THE CALCULATION OF HIGH-PRESSURE VISCOSITY FOR REFRIGERANT MIXTURES - Avsec, Jurij; Novosel, Urška (Journal of Energy Technology, 2024)
This paper features a mathematical model for computing the viscosity in the fluid domain for a hydrofluorocarbon mixture with the help of statistical thermodynamics. The viscosity pf HFC-134a (1,1,1,2-Tetrafluoroethane) and HFC-125 (Pentafluoroethane) mixtures was calculated as an example of hydrofluorocarbon mixtures. To calculate the thermodynamic properties of a real fluid, the models were applied based on the Lennard-Jones intermolecular potential. The analytical results obtained via statistical thermodynamics are compared with the experimental data and show relatively good agreement.